Legal Protection for Consumers in Non-Bank Sharia Mortgage Schemes: A Maqāṣid al-Sharī‘ah and National Regulatory Approach - Riza Zulfikar (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2025)
The development of the Sharia-based property industry in Indonesia has increased public interest in non-bank sharia mortgage schemes as an alternative for home financing that complies with Islamic principles. However, the implementation of these schemes lacks adequate specific regulations, resulting in suboptimal legal protection for consumers. Many face issues such as non-transparent contracts, unilateral actions by developers, and difficulties in dispute resolution due to the absence of sharia-based settlement mechanisms. This research aims to analyse consumer protection in non-bank Sharia mortgage schemes from the perspectives of positive law and maqāṣid al-sharī‘ah, and to formulate regulatory recommendations that are just, transparent, and aligned with Sharia values. This research adopts a normative juridical method through a formal literature study of applicable regulations, fatwas, and legal doctrines, combined with maqāṣid al-sharī‘ah analysis as a moral and ethical foundation. The findings reveal that the current level of protection falls short of ideal standards due to the lack of standardized contract models and sharia-based dispute resolution mechanisms. It is recommended that a collaborative regulatory framework be developed, prioritizing justice, transparency, and sustainability, to substantively safeguard consumer rights and enhance public trust in non-bank Sharia property financing systems.